ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KOMITE AUDIT, DAN BOOX TEXT DIFFERNCE TERHADAP PRESISTENSI LABA : STUDI PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI - Sella, Nivada Two; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the influence of Managerial Ownership, Audit Committee, and Book Tax Differences on Profit Persistence in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This research applied a quantitative approach using the purposive sampling method to produce 33 samples. The independent variables in the study include Managerial Ownership, Audit Committee, and Book Tax Differences, while Profit Persistence is the dependent variable. Data analysis in this study applies multiple linear regression tests. The results of this study show that Managerial Ownership has a significant positive influence on profit persistence, the Audit Committee has a significant negative influence on profit persistence, Book Tax Differences has a significant negative influence on profit persistence, and simultaneously, the three independent variables have a significant influence on profit persistence